Proposed new interior design of Microsoft Store for Microsoft (Malaysia) Sdn Bhd at Lot S-20, Level 1, The 19 Digital Mall, USJ 19, UEP Subang Jaya, Selangor / Mohd Alif Osman - Osman, Mohd Alif (Faculty of Architecture, Planning and Surveying, 2010)
Before the design process to take place, looking for problems in the design process needs to be done to identify problems so that a solution can be developed or determined. For my final project in Diploma in Interior Design, the title of my project is Proposed New Interior Design of Microsoft Store for Microsoft (Malaysia) Sdn Bhd located at Lot S-20, Level 1, The 19 Digital Mall, USJ 19, UEP Subang Jaya, Selangor. The first step before I started this project is find problems or issues through reading and observation has been done before. Searching and collecting information through of analysis and case study have done. Several important aspects must be considered to ensure the space function, such as to fulfill client, users and comfort. The client identity is important to thing in the design process because client is owner of the project, designer as the medium to create something base on fulfill of client. By creating this project, it is hoped that it will be able to give benefits to the visitors, society and country.